Abnormal Changes of Monocyte Subsets in Patients With Sjögren’s Syndrome - He, Yan; Chen, Rongjuan; Zhang, Mengqin; Wang, Bin; Liao, Zhangdi; Shi, Guixiu; Li, Yan (Frontiers in Immunology, 2022)
Background: Recent studies have proven the existence of distinct monocyte subsets, which play a significant role in the development of some rheumatic diseases such as systemic lupus erythematosus (SLE). This study was performed to define the changes of monocyte subsets in patients with Sjögren's Syndrome (SjS). Methods: Single cell RNA-sequencing (scRNA-seq) data of monocytes from SjS patients and controls were analyzed. The transcriptomic changes in monocyte subsets between SjS and controls were identified and potential key functional pathways involved in SjS development were also explored. Results: A total of 11 monocyte subsets were identified in the scRNA-seq analyses of monocytes. A new monocyte subset characterized by higher expression of VNN2 (GPI-80) and S100A12 (Monocyte cluster 3) was identified, and it was increased in SjS patients. Compared with controls, almost all monocyte subsets from SjS patients had increased expression of TNFSF10 (TRAIL). Moreover, interferon (IFN)-related and neutrophil activation-associated pathways were main up-regulated pathways in the monocytes of SjS patients. Conclusion: This study uncovered the abnormal changes in monocyte subsets and their transcriptomic changes in SjS patients, and identified TNFSF10 high/+ monocytes as a potential key player in SjS pathogenesis and a promising target for SjS treatment.